Domovi za stare - organizacija, delo, dosežki in problemi - Leskovic, Ljiljana (Zdravniški vestnik, 2004)
Growing numbers of elderly population and economic problems are the reason forthe country to accede changes of elderly politics. Unfortunately, we are not avare of the problem extensions that are bringing aging of society in our environment. We can not search for solutions only in assurance of available storage facility in institutional care. If we look back, we find that current development of social care for elderly in Slovenia is based largely on institutional care and by all means comparable with other developed European countries. But without further agreement about progress in different form of care, we will have to face problems that can not be solved.
Keywords: Aged; domovi za stare ljudi; Domovi za starostnike; Health Services For The Aged; Homes For The Aged; Legislation And Jurisprudence; Negovalni domovi; Nursing Homes; organizacija; organization; Organization And Administration; Slovenia; Slovenija; stari ljudje; Starostniki; Statistics And Numerical Data; Zdravstvene službe za starostnike